Tindakan Pertanahan Nasional dalam Menerapkan Asas Mutakhir Untuk Mengurangi Potensi Timbulnya Sertifikat Ganda atas Tanah (LEGAL DIALOGICA, 2025)
This study examines the National Land Agency's (BPN) implementation of the exchange principle to reduce the potential for duplicate land certificates. Duplicate or overlapping certificates constitute a crucial issue in the land sector, creating legal threats, property transactions, and even land mafia practices. The purpose of this study is to determine the role and actions of the BPN in realizing the progressive principle and to analyze efforts made to prevent duplicate certificates.The research used a juridical-sociological approach, conducted in Palu City, involving the BPN's Palu Regional Office, the Class IA District Court, and Land Deed Officials (PPAT). Data were obtained through interviews, literature review, and analysis of land-related regulations.The results indicate that the problem of duplicate certificates in Palu City was triggered by a weak manual data collection system in the past, regional expansion, lack of synchronization of data between sub-districts and the BPN, and the involvement of land mafia elements. To address these issues, the BPN implemented changes through land data updates, internal mediation, and the implementation of Ministerial Regulation No. 21 of 2020, as well as collaboration with the Land Mafia Task Force. Furthermore, Land Deed Officials (PPAT) play a role in prevention through document verification, certificate checking, and the application of the principle of prudence in every transaction.This research recommends that implementing the exchange principle is crucial for ensuring legal certainty over land. However, its successful implementation is still determined by technical and administrative factors, as well as limited authority. Therefore, strengthening an integrated land system, increasing oversight, and synergy between agencies are necessary to minimize the potential for duplicate certificates to be issued in the future.Abstrak:Penelitian ini membahas mengenai tindakan Badan Pertanahan Nasional (BPN) dalam menerapkan asas pertukaran untuk mengurangi potensi timbulnya sertifikat ganda atas tanah. Sertifikat ganda atau tumpang tindih sertifikat merupakan salah satu permasalahan krusial di bidang pertanahan karena menimbulkan ancaman hukum, transaksi kepemilikan, hingga praktik mafia tanah. Tujuan penelitian ini adalah untuk mengetahui peranan dan tindakan BPN dalam mewujudkan asas progresif serta menganalisis upaya yang dilakukan untuk mencegah timbulnya sertifikat ganda.Penelitian yang digunakan adalah pendekatan yuridis-sosiologis dengan lokasi penelitian di Kota Palu, melibatkan BPN Kantah Palu, Pengadilan Negeri Kelas IA, serta PPAT. Data diperoleh melalui wawancara, kajian kepustakaan, dan analisis peraturan-undangan terkait pertanahan.Hasil penelitian menunjukkan bahwa permasalahan sertifikat ganda di Kota Palu dipicu oleh lemahnya sistem pendataan manual di masa lalu, pemekaran wilayah, kurang sinkronnya data antara kelurahan dan BPN, serta keterlibatan oknum mafia tanah. Dalam menghadapi permasalahan tersebut, BPN menerapkan perubahan dengan pembaruan data pertanahan, mediasi internal, penerapan Permen ATR/BPN No. 21 Tahun 2020, serta kerja sama dengan Satgas Mafia Tanah. Selain itu, PPAT berperan dalam pencegahan melalui verifikasi dokumen, pengecekan sertifikat, serta penerapan prinsip kehati-hatian dalam setiap transaksi.Rekomendasi penelitian ini adalah bahwa penerapan asas pertukaran sangat penting untuk menjamin kepastian hukum atas tanah. Namun keberhasilan implementasinya masih ditentukan oleh faktor teknis, administratif, dan rendahnya kewenangan. Oleh karena itu, diperlukan penguatan sistem pertanahan yang terintegrasi, peningkatan pengawasan, serta sinergi antarinstansi guna meminimalisir potensi terbitnya sertifikat ganda di masa mendatang.